Analysis of Bacterial Pathogens Causing Complicating HAP in Patients with Secondary Peritonitis - Chudáček, Josef; Špička, Petr; Kolar, Milan; Stašek, Martin; Kolcún, Štefan; Klos, Dušan; Hricová, Kristýna; Mlynarcik, Patrik; Pudová, Vendula; Klementová, Olga; Horáček, Rostislav (Antibiotics (Basel, Switzerland), 2023)
BACKGROUND: Diffuse peritonitis is an acute abdominal condition characterized by high mortality. The main treatment modality is surgery, requiring a subsequent prolonged hospital stay. These patients are, among other things, at risk of developing hospital-acquired pneumonia (HAP), which considerably worsens their treatment outcomes. This study aimed to extend the existing knowledge by providing more detailed microbiological characteristics of complicating HAP in patients with secondary peritonitis, including the identification of isolated bacterial pathogens and their potential sources. METHODS: The 2015-2019 retrospective study comprised all patients with an intraoperatively confirmed diagnosis of secondary diffuse peritonitis who were classified in accordance with the quick Sepsis Related Organ Failure Assessment scoring system. RESULTS: HAP developed in 15% of patients. The 90-day mortality rates were 53% and 24% in patients with and without HAP; respectively. The most frequent pathogens responsible for HAP were Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Enterobacter cloacae complex and Enterococcus faecalis. Multidrug resistance to antibiotics was found in 38% of bacterial pathogens. Clonal spread of these bacterial pathogens among patients was not detected. Rather, the endogenous characteristic of HAP was confirmed. CONCLUSIONS: The initial antibiotic therapy of complicating HAP in patients with secondary peritonitis must be effective mainly against enterobacteria, including strains with the production of ESBL and AmpC beta-lactamases, Pseudomonas aeruginosa and Enterococcus faecalis. The study further highlighted the importance of monitoring the respiratory tract bacterial microflora in patients with secondary peritonitis. The results should be used for initial antibiotic treatment of complicating HAP instances.
Keywords: etiology; peritonitis; bacteria; pneumonia